A CRISPR/Cas9‐based method for seamless N‐terminal protein tagging in Saccharomyces cerevisiae. Issue 11 (6th September 2021) - Kira, Shintaro; Noda, Takeshi
Abstract: Protein tagging is an effective method for characterizing a gene of interest. Tagging can be accomplished in vivo in Saccharomyces cerevisiae by chromosomal integration of a PCR‐amplified cassette. However, common tagging cassettes are not suitable for in situ N‐terminal tagging when we aim to preserve the gene's endogenous promoter. Existing methods require either two rounds of homologous recombination or a relatively complex cloning process to construct strains with N‐terminal protein tags. Here, we describe a simple CRISPR/Cas9‐based method for seamless N‐terminal tagging of yeast genes that preserves their endogenous promoter. This method enables the generation of N‐terminally tagged strains by introducing an expression vector containing the cas9 gene and a specific gRNA for cleaving the 5′ end of the target gene's protein‐coding sequence, along with donor DNA containing the tag sequence and homology arms. gRNA cloning was executed by inverse PCR instead of the conventional method. After verifying the tag, the Cas9 and gRNA expression plasmids were eliminated without using antibiotic‐containing medium. By this method, we generated strains that express N‐terminally tagged subunits of the TORC1 protein kinase complex and found that these strains are comparable to strains made by conventional methods. Thus, our method provides a cost‐effective alternative for seamless N‐terminal tagging in baker's yeast. Take Away: We propose a CRISPR/Cas9‐based method for seamless N‐terminal tagging in Saccharomyces cerevisiae . Tagged proteins are expressed under the control of the endogenous promoter. This method requires only about 10 days for constructing a new strain. Drug selection is not required during the process, which makes it cost effective.